Trends in Nosocomial Bloodstream Infections following Health Care Restructuring in Alberta between 1999 and 2005 - Mao-Cheng Lee; Lynora Saxinger; Sarah E Forgie; Geoffrey Taylor (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: A previous study at the University of Alberta Hospital/Stollery Children’s Hospital in Edmonton, Alberta, revealed an increase in hospital-acquired bloodstream infection (BSI) rates associated with an increase in patient acuity during a period of public health care delivery restructuring between 1993 and 1996. The present study assessed trends in BSIs since the end of the restructuring.